## Evaluate -a – 12a^2 for a = -1 a. -13 b. 13 c.-11

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

C

substitute a = – 1 into the expression

– (- 1) – 12(- 1)² = 1 – (12 × 1 ) = 1 – 12 = – 11 → C

c because PEMDAS start with the exponents so (-1)^2 =1 times -12=-12 and –1=1 so we end up with 1-12 or -11 which is C